Studi Pengembangan Paket Perjalanan Wisata Yoga Bali Kuno di Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar - Arta Widana , I Ketut; Sudiana, I Gusti Ngurah; Surpi, Ni Kadek; Widyastuti, Ni Putu (Jayapangus Press, 2025)
This study aims to develop a travel package centered on Ancient Balinese Yoga, based at the Hindu State University of I Gusti Bagus Sugriwa Denpasar. The tourism package is designed to highlight Bali's spiritual heritage through yoga practices rooted in Hindu Dharma teachings and the local philosophy of the Watukaru tradition. The research employs an Ethnographic Content Analysis (ECA) approach to qualitative data obtained through in-depth interviews, observation of yoga practices, focus group discussions, and literature review. The findings reveal that Ancient Balinese Yoga possesses distinctive characteristics compared to other forms of yoga, particularly in its integration of movement (yogācāra), pranayama, mantra, and Balinese spiritual teachings. The development potential is reflected in four key aspects: uniqueness and authenticity, aesthetic value, spiritual value and character formation, as well as holistic health benefits. This study concludes that Ancient Balinese Yoga holds significant potential as an international spiritual tourism destination, contributing meaningfully to cultural preservation, the strengthening of Bali’s spiritual identity, and the advancement of educational and sustainable tourism.